The Perception of the Strawberry Generation Towards Political Literacy in the 2024 Election in Lubuk Basung, Agam Regency - Sitti Raudatuljannah; Nora Eka Putri (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This study aims to analyze the Perception of the Strawberry Generation Towards Political Literacy of the 2024 Election in Lubuk Basung, Agam Regency. the research method used in this research is Quantitative with Descriptive Analysis. this study took a sample of 100 people. this research data was processed and analyzed using the SPSS version 25 application for windows software and to see the validity and reliability of the data. The results of this study are that the indicators of the strawberry generation obtained around 83.4%, which means that they will be technologically literate, mentality vulnerable, like instant things and are active in browsing the internet in obtaining information about the political literacy of the 2024 elections in Lubuk Basung, Agam Regency. while the election political literacy indicator obtained around 74.5%, which means that the strawberry generation's perception of the political literacy of the 2024 elections in Lubuk Basung, Agam Regency has a good level of literacy regarding election political issues.